Basics of Radiation Biology When Treating Hyperproliferative Benign Diseases - Rödel, Franz; Fournier, Claudia; Wiedemann, Julia; Merz, Felicitas; Gaipl, Udo S.; Frey, Benjamin; Keilholz, Ludwig; Seegenschmiedt, M. Heinrich; Rödel, Claus; Hehlgans, Stephanie (Frontiers in Immunology, 2017)
For decades, low- and moderate dose radiation therapy has been shown to exert a beneficial therapeutic effect in a multitude of non-malignant conditions including painful degenerative muscoloskeletal and hyperproliferative disorders. Dupuytren and Ledderhose diseases are benign fibroproliferative diseases of the hand/foot with fibrotic nodules and fascial cords, which determine debilitating contractures and deformities of fingers/toes while keloids are exuberant scar formations following burn damage, surgery and trauma. Although radiation therapy has become an established and effective option in the management of these diseases, experimental studies to illustrate cellular composites and factors involved remain to be elucidated. More recent findings, however, indicate the involvement of radiation sensitive targets like mitotic fibroblasts/myofibroblasts as well as inflammatory cells. Radiation-related molecular mechanisms affecting these target cells include the production of free radicals to hamper proliferative activity and interference with growth factors and cytokines. Moreover, an impairment of activated immune cells involved in both, myofibroblast proliferative and inflammatory processes may further contribute to the clinical effects. We here aim at briefly describing mechanisms contributing to a modulation of proliferative and inflammatory processes and to summarize current concepts of treating hyperproliferative diseases by low and moderate doses of ionizing radiation.